Aerodynamic design of the high pressure and low pressure axial turbines for the improved coal-fired recompression SCO2 reheated Brayton cycle. (15th July 2019) - Han, Wanlong; Zhang, Yifan; Li, Hongzhi; Yao, Mingyu; Wang, Yueming; Feng, Zhenping; Zhou, Dong; Dan, Guangju
Abstract: A new type of improved coal-fired recompression SCO2 Brayton cycle with a second split flow to the boiler was introduced. The design parameters of the high and low pressure turbines of the above SCO2 Brayton cycle were determined based on a consideration of the economics of the SCO2 system and the realization of the equipment. The self-compiled mean-line design program for two-stage SCO2 axial turbines was used to design the high and low pressure turbines for the 5 MW SCO2 Brayton cycle, with the important design data of the two turbines being given. RANS equations and the SST Turbulence Model were chosen for numerical simulation of the aerodynamic performance of two turbines in the design point and variable operating conditions that used ANSYS CFX and the real physical property data file of SCO2 from NIST software. Numerical results indicated that the isentropic efficiency of the SCO2 high pressure turbine and low pressure turbine with a good variable operating performance are 82.88% and 82.26% in the design point, respectively. The output power of the high pressure turbine and low pressure turbine are 3, 251 kW and 6, 156 kW, respectively, in the design point, which can meet the design requirements. The Cps curves, limited streamline spectrums, and the Mach number contours of the root, middle and top flow field of the turbine blades is reasonable. Highlights: A new improved coal-fired recompression SCO2 Brayton cycle was introduced. Turbine design parameters were determined based on system economics and realization. RPG of CO2 was fully considered in design and numerical simulation of SCO2 turbines. Two axial two-stage SCO2 turbines were designed and the flow information was given.